PELATIHAN ADMINISTRASI PEMERINTAHAN SEBAGAI UPAYA PENINGKATAN KAPASITAS APARATUR PEMERINTAHAN DESA DAN MASYARAKAT DI DESA NANSEAN - Handrianus Vianey Melin Wula; Elpius Kalembang; Melkianus Suni (LPPM Universitas Timor, 2020)
This Community Service aims to increase the capacity of village officials and communities regarding village government administration and encourage orderly village service administration in Nansean Village, Insana District, North Central Timor Regency. The service method used is to convey material about village government administration, show and guide village officials in making village government administration books according to the guidelines. The result of this service activity is that the Nansean village apparatus can find out about the procedures for managing village government administration properly and most accurately which will produce accurate and complete data and information.Keywords: Village Government Administration, Capacity Building